Native T1 mapping and extracellular volume fraction measurement for assessment of right ventricular insertion point and septal fibrosis in chronic thromboembolic pulmonary hypertension. - Roller, Fritz; Wiedenroth, Christoph; Breithecker, Andreas; Liebetrau, Christoph; Mayer, Eckhard; Schneider, Christian; Rolf, Andreas; Hamm, Christian; Krombach, Gabriele; Roller, Fritz C; Krombach, Gabriele A (European Radiology, 2017)
Objectives: The aim of this study was to assess septal and right ventricular insertion point (RVIP) fibrosis in patients with chronic thromboembolic pulmonary hypertension (CTEPH) via native T1 mapping and extracellular volume fraction (ECV) determination and to analyze correlations with functional parameters.Methods: Imaging was performed at 1.5 Tesla in 24 patients diagnosed with CTEPH and 24 controls. T1 values were measured within the septal myocardium, the upper and lower RVIP, and the lateral wall at basal short axis section.Results: The mean septal native T1 values were 1012.8 ms ± 50.5 in the CTEPH group and 956.9 ms ± 24.4 in controls (p < 0.001), upper RIVP 1050.8 ms ± 64.2 vs. 965.3 ms ± 37.1 (p < 0.001), and lower RVIP 1084.4 ms ± 93.1 vs. 959.8 ms ± 40.4 (p < 0.001). The corresponding mean ECV values were also significantly increased in the CTEPH group (p < 0.001). Native septal T1 showed a strong negative correlation with right ventricular ejection fraction (k = -0.92; p = 0.01).Conclusions: We conclude that native T1 mapping and ECV assessment enable visualization and quantification of septal fibrosis in CTEPH patients. The results also correlate well with right ventricular ejection fraction. Therefore, these parameters might be useful for prognosis and as therapy-monitoring tool in the future.Key Points: • Septal native T1 and ECV values are significantly higher in CTEPH patients. • Native T1 and ECV values are elevated even in absence of LGE. • These techniques therefore enable an improved quantification of septal fibrosis in CTEPH. • Native T1 values also correlate well with right ventricular EF and PA-pressure. • Prognosis and therapy-monitoring might be assessable in the future with these parameters.